Download presentation
Presentation is loading. Please wait.
1
The Order of Operations
2
The Order of Operations
Consider the expression, x 4
3
The Order of Operations
Consider the expression, x 4 Evaluate the expression by doing the multiplication first.
4
The Order of Operations
Consider the expression, x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = = 22
5
The Order of Operations
Consider the expression, x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = = 22 Evaluate the expression by doing the addition first.
6
The Order of Operations
Consider the expression, x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = = 22 Evaluate the expression by doing the addition first. = 7 x 4 = 28
7
The Order of Operations
Consider the expression, x 4 Evaluate the expression by doing the multiplication first. 2 + 5 x 4 = = 22 Evaluate the expression by doing the addition first. = 7 x 4 = 28 We need rules!
8
The Order of Operations
BEDMAS
9
The Order of Operations
BEDMAS B E DM AS
10
The Order of Operations
BEDMAS B - Do operations in brackets first. E DM AS
11
The Order of Operations
BEDMAS B - Do operations in brackets first. E - Evaluate exponents next. DM AS
12
The Order of Operations
BEDMAS B - Do operations in brackets first. E - Evaluate exponents next. DM - Do dividing and multiplying in the order they appear. AS
13
The Order of Operations
BEDMAS B - Do operations in brackets first. E - Evaluate exponents next. DM - Do dividing and multiplying in the order they appear. AS - Do adding and subtracting in the order they appear.
14
The Order of Operations
BEDMAS Ex) (-3) x (-5) + (+18) ÷ (-3)
15
The Order of Operations
BEDMAS Ex) (-3) x (-5) + (+18) ÷ (-3) = (+15) + (-6)
16
The Order of Operations
BEDMAS Ex) (-3) x (-5) + (+18) ÷ (-3) = (+15) + (-6) = (+9)
17
The Order of Operations
BEDMAS Ex) [(-8) – 15] x (-2)
18
The Order of Operations
BEDMAS Ex) [(-8) – 15] x (-2) = [(-8) + (-15)] x (-2)
19
The Order of Operations
BEDMAS Ex) [(-8) – 15] x (-2) = [(-8) + (-15)] x (-2) = (-23) x (-2)
20
The Order of Operations
BEDMAS Ex) [(-8) – 15] x (-2) = [(-8) + (-15)] x (-2) = (-23) x (-2) = (+46)
21
The Order of Operations
BEDMAS Ex) [(+4) + (-3)2 – 23]2
22
The Order of Operations
BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2
23
The Order of Operations
BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2 = [(+4) + 9 – 8]2
24
The Order of Operations
BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2 = [(+4) + 9 – 8]2 =
25
The Order of Operations
BEDMAS Ex) [(+4) + (-3)2 – 23]2 = [(+4) + (-3) x (-3) – 2 x 2 x 2]2 = [(+4) + 9 – 8]2 = =
26
The Order of Operations
Ex) (-4)2 + (-2)(-3) 7 + (-9)
27
The Order of Operations
Ex) (-4)2 + (-2)(-3) 7 + (-9) = -2
28
The Order of Operations
Ex) (-4)2 + (-2)(-3) 7 + (-9) = -2 = 22
29
The Order of Operations
Ex) (-4)2 + (-2)(-3) 7 + (-9) = -2 = 22 = -11
30
The Order of Operations
Ex) (-4)2 + (-2)(-3) 7 + (-9) = -2 = The numerator and denominator must be evaluated before dividing. = -11
31
The Order of Operations
Ex) (-4)2 + (-2)(-3) 7 + (-9) = -2 = The numerator and denominator must be evaluated before dividing. = It’s as if they were in brackets.
32
The Order of Operations
Is there a difference between the following? (-3)4 and -34 = (-3)(-3)(-3)(-3) = (+9)(-3)(-3) = (-27)(-3) = (+81) -34 = -(34) = -(3 x 3 x 3 x 3) = Yes there is a difference. Ask, “What is the base of the power?”
33
The Order of Operations
Evaluate the following expression when x = 3 and y = -2 4x2 – (5 + y3) = 4(3)2 – (5 + (-2)3) = 4(9) – (5 + (-8)) = 36 – (-3) = (+3) = 39 jjjjjjjj
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.